A new coevolution process for conceptual design. Issue 1 (2015) - Liu, Ang; Lu, Stephen C.-Y.
Abstract Conceptual design involves coevolution of decisions between functional and physical domains. Different methods prescribe different processes to achieve coevolution, hence are suitable for different kinds of design practices. Analytical Target Cascading (ATC) features successive decompositions followed by coordinated optimizations to improve existing systems. Axiomatic Design Theory (ADT) follows a back-and-forth zigzagging process to create completely new systems. A new coevolution process, which is a hybrid between ATC and ADT, is developed from our Innovative Design thinking (IDT) research. This paper explains its theoretical underpinnings and illustrates its suitability for practices between the two extremes, e.g., innovative design on existing systems.